Massive Volume of Unstructured Data and Storage Space Optimization- a Review - V. Powar, Ranjeet; Arunkumar, B (International Journal of Engineering and Technology, 2018)
Nowadays the volume of digital data generated and used by enterprises is increasing at an enormous rate. The survey says that more than 80% of data that were generated in the last two years are unstructured in nature. Hence storage space requirement for storing this big volume of unstructured data is very high.Â It has gained attention to large-scale storage systems. Deduplication is a space efficient method mainly used to solve storage space optimization problem. This paper focuses on the effect of massive volume of unstructured data and review various storage optimization techniques and survey of various storage types. In addition, it elaborates specific challenges with regard to storage optimization using deduplication and technology that handles a huge amount of unstructured data.Â Â